Cognitive Behavioral Therapy and Clinical Applications 2018
DOI: 10.5772/intechopen.70612
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy of Obsessive-Compulsive Disorder in Children and Adolescents

Abstract: While obsessive-compulsive disorder (OCD) is present under the category of anxiety disorders in DSM-IV TR, it is classified under "Obsessive Compulsive Disorder and Related Disorders" in DSM 5. There is no different diagnostic system for children and adolescents. OCD has serious adverse effects on family, school, and social lives of children and adolescents, but adolescents with OCD often hide their symptoms and delay seeking help due to several reasons such as inability to recognize their symptoms as disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…This study also demonstrated that youth who perceived less impairment than their parent at baseline experienced less symptom improvement at post-treatment, and that poor insight at post-treatment was associated with lack of symptom improvement. In other studies, poor insight has also been found to be associated with poor response to both drug treatment and psychotherapy for adults and children with OCD [34], [48], [56], [57]. Regardless of age, low clinical insight may diminish motivation and commitment to therapy, thus creating problems for therapeutic homework completion and treatment gains [45], [58].…”
Section: Treatment Outcomes Across the Life Coursementioning
confidence: 91%
See 1 more Smart Citation
“…This study also demonstrated that youth who perceived less impairment than their parent at baseline experienced less symptom improvement at post-treatment, and that poor insight at post-treatment was associated with lack of symptom improvement. In other studies, poor insight has also been found to be associated with poor response to both drug treatment and psychotherapy for adults and children with OCD [34], [48], [56], [57]. Regardless of age, low clinical insight may diminish motivation and commitment to therapy, thus creating problems for therapeutic homework completion and treatment gains [45], [58].…”
Section: Treatment Outcomes Across the Life Coursementioning
confidence: 91%
“…Importantly, age is inversely associated with insight, meaning children with OCD display poorer insight than adolescents and adults with OCD [32]. Specifically, it is estimated that approximately 9-30% of adults diagnosed with OCD have poor insight into their symptoms [33], whereas some studies have placed the prevalence of poor insight in children with OCD to be as high as 45% [34], [35]. Because of these figures, many clinicians associate poor insight with children more often than with adults.…”
Section: Clinical Correlates Across the Life Coursementioning
confidence: 99%